Giai pt:\(\sqrt{\left(5-2\sqrt{6}\right)^x}+\sqrt{\left(5+2\sqrt{6}\right)^x}=10\)
Giai pt: \(\sqrt{\left(5-2\sqrt{6}\right)^x}+\sqrt{\left(5+2\sqrt{6}\right)^x}=10\)
Giải PT sau: \(\left(2-\sqrt{5}\right)\)x2 + \(\left(6-\sqrt{5}\right)\)x \(-\) \(8\) + \(2\sqrt{5}\) = 0
Giải phương trình: \(\sqrt{\left(5-2\sqrt{6}\right)^x}+\sqrt{\left(5+2\sqrt{6}\right)^x}=10\)10
Giải pt \(\left(\sqrt{x+3}+\sqrt{6-x}\right)\left(6\sqrt{2x+6}-2x-13\right)=6\sqrt{2}\)
giải pt \(\sqrt{3x^2-6x-6}=3\sqrt{\left(2-x\right)^5}+\left(7x-19\right)\sqrt{2-x}\)
Giải phương trình
\(\sqrt{\left(5+2\sqrt{6}\right)^x}+\sqrt{\left(5-2\sqrt{6}\right)^x}=10\)
giải hệ pt \(\int^{x+y+xy=5}_{\left(x+1\right)^3+\left(y+1\right)^3=35}\)
giải pt \(\sqrt{\left(3+2\sqrt{2}\right)^x}+\sqrt{\left(3-2\sqrt{2}\right)^x}=6\)
\(\left(6\right)\dfrac{3\sqrt{x}}{5\sqrt{x}-1}\le-3\)
\(\left(7\right)\dfrac{8\sqrt{x}+8}{6\sqrt{x}+9}>\dfrac{8}{3}\)
\(\left(8\right)\dfrac{\sqrt{x}-2}{2\sqrt{x}-3}< -4\)
\(\left(9\right)\dfrac{4\sqrt{x}+6}{5\sqrt{x}+7}\le-\dfrac{2}{3}\)
\(\left(10\right)\dfrac{6\sqrt{x}-2}{7\sqrt{x}-1}>-6\)